Cretaceous planktonic foraminifera biozonation and correlations - M.R. Petrizzo (2011)
Introduction explaining the main problems Comments on the applicability of the common used low latitude biozonations (Premoli Silva and Sliter, 1995; Robaszynski and Caron, 1995). Correlation problems among sections are mainly related to: - erroneous and/or ambiguous species concepts adopted and/or poor preservation of the type material (holotype, paratype) = TAXONOMIC REVISION IN PROGRESS by the Mesozoic Planktonic Foraminifera Working Group - difficulty in identifying the first occurrences of gradually evolving species (ex. H. helvetica - early Turonian) - homeomorphy and diachronous distributions (ex. G. ventricosa, A. mayaroensis) - problems with high latitude correlation because of the absence of the low latitude marker taxa (ex. R. calcarata) - reliability of the bioevents when rare species are used as marker species (ex. G. aegyptiaca) - reproducibility of the data even in sections located in the same paleogeographic area. Work in progress: the ongoing revision of the planktonic foraminifera biozonation is focused on a better understanding of the reliability of the bioevents by testing the reproducibility of the data (sequence of bioevents) in stratigraphic sections located in different paleogeographic area. Examples presented and discussed: A) Lower Campanian = redefinition of the G. elevata Zone and definition of the new low-mid Campanian C. plummerae Zone (replacing the G. ventricosa Zone) calibrated against nannofossil and magnetostratigraphy. Stratigraphic sections analyzed: Bottaccione, Shatsky Rise, Tanzania, Caribbean Sea. B) Lower Turonian - upper Santonian = identification of new reliable bioevents to increase the resolution of the planktonic foraminiferal biozones (ex. M. schneegansi and D. concavata). Analysis of the most reliable and reproducible sequence of planktonic foraminiferal and calcareous nannofossils bioevents. Stratigraphic sections analyzed: Tanzania, Bottaccione, Kaalat Senan, Exmouth Plateau.